Analisis Performansi Routing Protokol Ad-Hoc on Demand Distance Vector (AODV) dan Greedy Perimeter Coordinator Routing (GPCR) Terhadap Data Collision Pada Vehicular Ad-Hoc Network (VANET) - Tyo Enos Revan Gultom; Heru Nurwarsito (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
VANET is a network that utilizes vehicles as nodes to exchange information and provides security and comfort for vehicle users. Its main characteristics are High Mobilility and Dynamic Network Topology. This characteristic allows data collision to occur, which is a condition where two or more nodes send data to the same destination at the same time. This situation causes the data transferred does not reach its destination so that the VANET function can be disrupted. Previous research stated that AODV is a better topology-based protocol compared to DSR and DSDV while GPCR is a position-based protocol with better performance than GPSR. This study presents an analysis of the effect of the two routing protocols on data collision and their performance analysis. Testing is based on changes in the number and speed of nodes with performance parameters throughput, packet delivery ratio (PDR), end-to-end delay, and collision rate. The results showed that the relationship between the two routing protocols to the collision rate was more dominantly affecting the results of the packet delivery ratio parameters. In performance analysis, AODV better at throughput and PDR with 48,05 kbps and 49,82 % while GPCR with 0,66 kbps and 7,3 % when there is a change in the number of nodes. When the node speed changes, throughput and PDR of AODV are 51,32 kbps and 33,34 % while GPCR are 0,585 kbps and 9,85 %. In end to end delay, GPCR is much better than AODV. On changes in the number and speed of nodes, each values ​​of AODV are 792.717 ms and 233.245 ms, and the values of GPCR are 14.528 ms and 5.252 ms.